2018
DOI: 10.1002/glia.23568
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus Type‐1 single‐stranded RNA activates the NLRP3 inflammasome and impairs autophagic clearance of damaged mitochondria in human microglia

Abstract: Despite the availability of antiretroviral therapy (ART) that fully suppresses human immunodeficiency virus type-1 (HIV), markers of inflammation and minor neurocognitive impairment are frequently identified in HIV-infected persons. Increasing data support that low level replication defective viral RNA is made by infected cells despite the absence of infectious virus. Specific GU-rich single-stranded RNA from the HIV long terminal repeat region (ssRNA40) signaling through toll-like receptor (TLR)-7 and -8 has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 80 publications
2
53
0
Order By: Relevance
“…Mitochondria damage is also a crucial activator of the NLRP3 inflammasome. Similar to lysosomal or endosomal maturation, mitochondria damage also induces the production of ROS to activate the NLRP3 inflammasome (56,57). The RIP1-RIP3 complex, assembled after viral infection, induces activation of the GTPase DRP1.…”
Section: Dampsmentioning
confidence: 99%
“…Mitochondria damage is also a crucial activator of the NLRP3 inflammasome. Similar to lysosomal or endosomal maturation, mitochondria damage also induces the production of ROS to activate the NLRP3 inflammasome (56,57). The RIP1-RIP3 complex, assembled after viral infection, induces activation of the GTPase DRP1.…”
Section: Dampsmentioning
confidence: 99%
“…Indeed, IAV recognition by the NOD receptor induces mitophagy, therefore restraining inflammasome activation ( 116 ). During HIV-1 infection, abortive infection of astrocytes or infection of microglial cells triggers inflammasome activation ( 142 ). However, in productive infection of astrocytes, mitophagy is induced and regulates this process ( 117 ).…”
Section: Viral Manipulation Of Autophagy-dependent Regulation Of Innamentioning
confidence: 99%
“…For example, in in vitro experiments on human primary neurons (HPNs) and microglial cells (HFMG) collected from healthy patients, it was discovered that treatment of the cells with HIV ssRNA40 (specific GU-rich single-stranded RNA from the HIV long terminal repeat region) activates the NLRP3 inflammasome and increases the expression and extracellular secretion of pro-inflammatory cytokines (IL-1β, IL-18) and neurotoxic cytokines (TNF-α, IL-1α, C1q). HIV ssRNA40 causes a blockade of autophagy/mitophagy-mediated negative regulation of NLRP3 inflammasome activity with the release of inflammatory cytokines, caspase-1 activation, and pyroptotic microglial cell death [ 22 ]. Another report has shown that HIV-1 induces the expression of NLRP3 inflammasome and IL-1β secretion in dendritic cells from healthy individuals but not HIV-1-infected patients, suggesting that inflammasome activation contributes to disease progression [ 23 ].…”
Section: Interplays Between Inflammasomes and Virusesmentioning
confidence: 99%
“… [ 17 ] HIV ssRNA40 Activates the NLRP3 inflammasome and increases the expression and extracellular secretion of pro-inflammatory cytokines (IL-1β, IL-18) and neurotoxic cytokines (TNF-α, IL-1α, C1q). [ 22 ] SARS-CoV E, ORF3a and ORF8b viroporin proteins SARS-CoV E induces Ca2+ leakage to the cytosol from Golgi storage and ORF3a protein induce K + efflux at the plasma membrane to the extracellular spaces. The imbalance in the ionic concentration in the cells, generated by damaged mitochondria ROS lead to NLRP3 inflammasome activation.…”
Section: Factors Responsible For Inflammasomes Activitymentioning
confidence: 99%